What is race? four philosophical views - Glasgow, Joshua; Haslanger, Sally Anne; Jeffers, Chike 1982- (Oxford University Press, 2019)
" Across public discourse, in the media, politics, many branches of academic inquiry, and ordinary daily interactions, we spend a lot time talking about race: race relations, racial violence, discrimination based on race, racial integration, racial progress. It is fair to say that questions about race have vexed our social life. But for all we speak about race, do we know what race is? Is it a social construct or a biological object? Is it a bankrupt holdover from a time before sophisticated scientific understanding and genetics, or can it still hold up in biological, genetic, and other types of research? Most fundamentally, is race real? In this book, four prominent philosophers and race theorists debate how best to answer these difficult questions, applying philosophical tools and the principles of social justice to cutting-edge findings from the biological and social sciences. Each presents a distinct view of race: Sally Haslanger argues that race is a socio-political reality. Chike Jeffers maintains that race is not only political but also, importantly, cultural. Quayshawn Spencer pursues the idea that race is biologically real. And Joshua Glasgow argues that either race is not real, or if it is, it must be real in a way that is neither social nor biological. Each offers an argument for their own view and then replies to the others. Woven together, the result is a lively debate that opens up numerous ways of understanding race. Above all, it is call for sophisticated and principled discussion of something that significantly permeates our lives. "--